Affect of Elastic Displacement Limiter on Shock Response of Double-stage Vibration Isolation System. (September 2020) - Gong, Yufeng; Peng, Weicai; Liu, Zhizhong
Abstract: With a certain shock load, the displacement of the equipment with double-stage vibration isolation mounting may exceed the deformation limits of isolators themselves. Therefore, elastic displacement limiters usually need to be used in order to limit the relatively large displacement. In this paper, the response of the double-stage vibration isolation system was studied by numerical method. Effects of stiffness and assembled clearance of elastic displacement limiter on shock response were discussed.